Therapist Self-Disclosure and Cultural Empathy from the Perspective of Racial-Ethnic Minority Clients - Ally, Ameena (Université d'Ottawa | University of Ottawa, 2025)
The purpose of this study was to explore the experience of racial/ethnic minority (REM) clients during therapy when their therapist self-disclosed something personal to them. The literature suggests that therapist self-disclosure (TSD) with REM clients may play a role in cultural empathy, that is when a therapist responds to differences and similarities between them and the client in a way that can contribute beneficially to the quality of and dynamics within the therapeutic relationship. As little is known about the relationship between therapist disclosure and cultural empathy, the research question for this qualitative study was: “What are REM clients’ experiences of cultural empathy during cross-cultural counselling when their therapist self-discloses to them?”. To this end, I conducted a narrative inquiry to obtain rich stories of cultural empathy from REM clients who have experienced TSD during cross-cultural counselling. I audio-recorded interviews with four participants who were cis-gender women ranging from their early 20s to mid-to-late-30s. I analyzed the transcribed interviews using Braun and Clark’s (2006) Thematic Analysis. I generated several themes that followed a narrative structure, including client cultural context, expectations about therapy, therapy process, experiences of TSD, definitions of cultural empathy, and reflections about therapy. I used the themes to organize and develop participant narratives as the output of the results. I offered my interpretations of participants’ experiences using tenets of relational-cultural theory. The narratives garnered from this study contributed to the currently limited understanding of REM client perspectives, their experience of TSD in a cross-cultural context, and the potential role of TSD in therapists conveying cultural empathy. It is my hope that these narratives will deepen the understanding of culturally responsive therapy and improve the quality of care that racial/ethnic minority clients receive.
Keywords: therapist self-disclosure; self-disclosure; racial-ethnic minority; cultural empathy; counselling; psychotherapy; therapist; multicultural; broaching; relational-cultural theory; narrative; thematic analysis